Informal Reasoning and Burden of Proof - BAILENSON, JEREMY N.; RIPS, LANCE J. (Applied cognitive psychology, 1996)
Informal arguments occur in casual discourse and typically feature participants trying to convince each other (or a third party) of their positions. As an argument progresses, one participant can accrue more burden of proof—will have to do more to prove he or she is correct. Some past studies have shown that evidence presented first is more effective than later evidence (primacy), while others have found that evidence presented last is more effective (recency). These studies largely focused on lists of evidence, however, and not on structured, persuasive dialogues. In the current experiments, subjects read dialogues between two speakers having a dispute. They then chose the participant with the greater burden of proof. The results demonstrated that burden of proof increases for the participant who offers the first claim in an argument (anti‐primacy) and sometimes decreases for the participant who offers a final challenge (e.g., What's your evidence?). These results suggest strategies that can help participants gain advantages in disputes and that may assist judges in avoiding bias while evaluating arguments. © 1996 John Wiley & Sons, Ltd.